(untitled) (Constructionism Conference Proceedings, 2025)
Chatbots such as ChatGPT and Claude can be asked to create apps. But it works well only if you ask for something simple and then iteratively ask for improvements, test them, and provide feedback. Learners with no programming experience can co-create web apps that can run in their browser and can incorporate any JavaScript library or API for capabilities such as speech, 3D graphics, computer vision, data analysis, pre-trained AI models, and machine learning. You can also ask for text-based adventures and all sorts of discussions including conversations between historical figures, participation in panel discussions and debates, and co-creation of illustrated stories.